1987
DOI: 10.1203/00006450-198707000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adrenocorticotropin, Cortisol, and Dehydroepiandrosterone Response to Corticotropin-Releasing Factor in Normal Children during Pubertal Development

Abstract: ABSTRACT. The adrenocorticotropin (ACTH), cortisol, and dehydroepiandrosterone responses to synthetic human corticotropin-releasing factor (CRF) were studied in 28 endocrinologically healthy children (age 1-16 yr) and in six adult volunteers (age 24-42 yr). CRF was given as an intravenous bolus (I pg/kg body weight) between 0900 and 1000 hr. Significant increments in ACTH and cortisol levels after CRF were observed in all subjects, with an ACTH peak value of 48.2 2 3.4 pg/ml at 10 min Cp < 0.001). The ACTH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Although the majority of children in our study had peak ACTH levels by 15 min, we speculate that peak ACTH response may occur even earlier based on past studies of cortisol response at 10 min (22). These results are also consistent with the findings of Attanasio et al (16), who reported peak ACTH at 10 min and peak cortisol at 15-30 min. Among the most intriguing findings from this study were the significant correlations among the three different stress measures (nocturnal cortisol, CRH-F, and sleep maintenance).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although the majority of children in our study had peak ACTH levels by 15 min, we speculate that peak ACTH response may occur even earlier based on past studies of cortisol response at 10 min (22). These results are also consistent with the findings of Attanasio et al (16), who reported peak ACTH at 10 min and peak cortisol at 15-30 min. Among the most intriguing findings from this study were the significant correlations among the three different stress measures (nocturnal cortisol, CRH-F, and sleep maintenance).…”
Section: Discussionsupporting
confidence: 83%
“…Exaggerated ACTH responses to CRH stimulation help differentiate Cushing's disease from other causes of hypercortisolism, including primary affective disorders (4, 10-12). Previous reports have described responses in normal children (1 3) to ovine CRH administered in the evening, and responses in obese children or "normal" short children to human CRH administered in the morning (14)(15)(16). This report provides well-controlled normative data on ACTH and cortisol response to human CRH administered in the evening as well as baseline nocturnal cortisol levels.…”
mentioning
confidence: 93%
“…Our present findings showing that the ACTH-releasing activity of HEX increases at puberty, goes down in adulthood and then shows again a trend toward increase in aging, strengthen the hypothesis that a CRH-mediated mechanism does not mediate the ACTH-releasing activity of HEX. In fact, the CRHinduced ACTH response has been reported to be similar in prepubertal and pubertal children as well as in young adults (45). On the other hand, estrogens could play a role even in the increased corticotrope response to GHRPs at puberty; in fact, in animals there is evidence pointing to a role of sex steroids in the regulation of the HPA axis (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Corticotropin-releasing hormone (CRH) is a useful agent for evaluating the function of the hypothalamic-pituitaryadrenal axis and has been applied to normal subjects as well as patients with disorders of the hypothalamus, pituitary gland and adrenals [1,7,15,16,18]. There are few reports regarding hormonal assessments in children with brain neoplasms using CRH other than in those with Cushing disease [4,20].…”
Section: Introductionmentioning
confidence: 99%